2008
DOI: 10.1158/0008-5472.can-07-5156
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D3 (PKD3) Contributes to Prostate Cancer Cell Growth and Survival Through a PKCε/PKD3 Pathway Downstream of Akt and ERK 1/2

Abstract: Protein kinase D (PKD) is a family of novel diacylglycerol/ phorbol ester targets that regulate many important cellular functions including cell growth and survival. We now provide experimental evidence to indicate that PKD3 contributes to prostate cancer cell growth and survival. Expression of PKD3 as well as PKD1 was significantly higher in human prostate tumors compared with normal tissues as revealed by immunohistochemistry. Moreover, PKD3 exhibited a marked increase in nuclear localization in tumor tissue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
158
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(170 citation statements)
references
References 45 publications
11
158
1
Order By: Relevance
“…Overexpression of catalytically active PKD3 resulted in the hyperactivation of S6K1, whereas PKD3 knockdown reduced S6K1 phosphorylation. Interestingly, we did not observe any changes in the phosphorylation of Erk1/2 and Akt, kinases whose activation has previously been implicated in the context of PKD3-positive prostate cancer (10), indicating a selective effect of PKD3 on S6K1 in breast cancer cells. The two main S6K1 isoforms, p70 and p85, derive from the same gene and are produced by alternative translational initiation (16).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Overexpression of catalytically active PKD3 resulted in the hyperactivation of S6K1, whereas PKD3 knockdown reduced S6K1 phosphorylation. Interestingly, we did not observe any changes in the phosphorylation of Erk1/2 and Akt, kinases whose activation has previously been implicated in the context of PKD3-positive prostate cancer (10), indicating a selective effect of PKD3 on S6K1 in breast cancer cells. The two main S6K1 isoforms, p70 and p85, derive from the same gene and are produced by alternative translational initiation (16).…”
Section: Discussioncontrasting
confidence: 47%
“…For example, PKD1/2-mediated phosphorylation of substrates such as slingshot homolog 1 and Ras and Rab interactor 1 leads to the inhibition of cell migration (6 -8), and reduced PKD1 expression levels were observed by immunohistological analyses of invasive breast cancer samples (9), suggesting that the loss of PKD1 may be associated with breast tumor progression. By contrast, Chen et al (10) showed that PKD3 is up-regulated in primary prostate cancers and prostate cancer cell lines and stimulates prosurvival pathways, indicating a positive correlation between PKD3 expression and tumorigenesis. This implies that PKD3 regulates a distinct set of substrates to fulfill such functions, which is in accordance with our recent findings that PKD3 selectively phosphorylates the multidomain protein GIT1 (G-protein coupled receptor kinase-interacting protein 1) to enhance cell spreading and motility (11).…”
Section: Protein Kinase D (Pkd)mentioning
confidence: 90%
See 1 more Smart Citation
“…Prostate cancer cell lines exhibit increased levels of PKD3 and the degree of PKD3 nuclear localization has been positively correlated with tumor grade. PKD3 overexpression was also associated with increased growth and decreased apopotosis (48). These studies highlight the variable roles of the PKD isoforms in cancer biology and underline the importance of a more targeted and selective approach to anti-PKD therapeutics.…”
Section: Pkd and Tumor Angiogenesismentioning
confidence: 66%
“…21,22 A series of evidence from the chemical inhibitions, RNA interferences, and transfections of dominant negative mutants and the constitutive activated forms of several representative PKCs strongly validated that PKCe is required for suppression of onzin expression by PMA. Furthermore, PKCs lead to the activation of the MAPK pathway by multiple signaling molecules such as protein kinase D, 23,24 which stimulates phosphorylation of transcription factors or inhibitors, for example AP-1, c-Jun, and Elk, finally regulating gene expression. For instance, PKCe inhibits human CYP11B2 gene expression through ERK1/2 signaling pathway and Jun B.…”
Section: Discussionmentioning
confidence: 99%